2018
DOI: 10.1177/0887403417725370
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Police Enforcement Actions on Violent Crime: Evidence From a Saturation Foot-Patrol Intervention

Abstract: The current study tests the crime prevention effect of different police actions conducted during a foot-patrol saturation initiative in Newark, New Jersey. Police actions were categorized into two typologies: enforcement actions (i.e., arrests, quality of life summonses and field interrogations) and guardian actions (i.e., business checks, citizen contacts, bus checks, and taxi inspections). Logistic regression models tested the effect of enforcement and guardian actions on crime during daily (i.e., 24-hr) per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…Given the range of activities conducted during place‐based policing interventions, it is difficult to determine the precise officer activities that most directly generate crime reductions (Haberman, 2016). Certain studies provide evidence that crime decreases can result from traditional law enforcement activities, such as arrests, field stops, and citations (e.g., Piza, Caplan, Kennedy, & Gilchrist, 2015; Rosenfeld, Deckard, & Blackburn, 2014; Sherman & Rogan, 1995), whereas others indicate focused policing can generate significant crime reductions absent reliance on traditional enforcement actions (e.g., Ariel, Weinborn, & Sherman, 2016; Braga, Welsh, & Schnell, 2015; Piza, 2018b). This latter research illustrates a prevention mechanism through which police officers de‐emphasize formal enforcement in favor of conspicuous presence and more informal community engagement (Nagin, Solow, & Lum, 2015).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Given the range of activities conducted during place‐based policing interventions, it is difficult to determine the precise officer activities that most directly generate crime reductions (Haberman, 2016). Certain studies provide evidence that crime decreases can result from traditional law enforcement activities, such as arrests, field stops, and citations (e.g., Piza, Caplan, Kennedy, & Gilchrist, 2015; Rosenfeld, Deckard, & Blackburn, 2014; Sherman & Rogan, 1995), whereas others indicate focused policing can generate significant crime reductions absent reliance on traditional enforcement actions (e.g., Ariel, Weinborn, & Sherman, 2016; Braga, Welsh, & Schnell, 2015; Piza, 2018b). This latter research illustrates a prevention mechanism through which police officers de‐emphasize formal enforcement in favor of conspicuous presence and more informal community engagement (Nagin, Solow, & Lum, 2015).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…A randomized control trial of police foot patrols in Philadelphia circa summer 2009 found a significant reduction in violent crime after 12 weeks (Ratcliffe et al 2011). Newark's 2008Newark's -2009 Project Impact initiative (Piza 2018;Piza & O'Hara 2014), which combined both proactive "enforcement actions" and more sentinel-like "guardian actions" of foot patrols, also yielded generally positive results. Piza and O'Hara's (2014) results indicate total street violence was reduced.…”
Section: Police Staffingmentioning
confidence: 99%
“…Hot-spot policing is a policing strategy based on sites in which traditional policing strategies, such as increasing the number of police officers and arrests, are implemented in places where crime rates are disproportionately higher than in other locations within a jurisdiction (Braga et al, 2012; Telep and Weisburd, 2012; Weisburd and Eck, 2004; Santos, 2014; Novak et al, 2016; Grossrieder et al, 2017; Ariel and Partridge, 2017; Piza, 2018; Andresen and Hodgkinson, 2018; Mugari and Thabana, 2018; Koche and Weisburd, 2018; Haberman and Stiver, 2019; Schaefer et al, 2019). According to Santos (2014), the research on the efficacy of hot-spot policing is rigorous and abundant, such as the study on patrols led by uniformed private security guards to fight street violence in the Swedish city of Örebro (Frogner et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In general, studies have identified the following four types of strategies used by law enforcement agencies in various contexts: the Standard Model of Policing (Telep and Weisburd, 2012; Santos, 2014); Community Policing (Suve et al, 2015; Lobnikar et al, 2016; Saberi, 2017; Crowl, 2017; Musuguri, 2018; Spasić and Radovanović, 2019; Harrison and Gill, 2019); Problem-oriented policing (Porter and Graycar, 2016; Carson and Wellman, 2018; Factor, 2018; Goldstein, 2018; Kailemia, 2019); and hot spot policing (Novak et al, 2016; Grossrieder et al, 2017; Ariel and Partridge, 2017; Piza, 2018; Andresen and Hodgkinson, 2018; Mugari and Thabana, 2018; Koche and Weisburd, 2018; Haberman and Stiver, 2019; Schaefer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%